2024
DOI: 10.24084/repqj10.623
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Generalized Non-Active Power Theory for Compensation of Non-Periodic Disturbances

Abstract: Abstract.The principle and analysis of usage of the generalized non-active power theory for the parallel compensation of periodic and non-periodic current disturbances is presented in the paper. A non-linear unbalanced load generating periodic as well as non-periodic stochastic currents connected to an unsymmetrical non-sinusoidal voltage source is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There is research on the influence of this time interval, depending on the compensation objective [146,193,194]. Implementations based on GINAP theory in the control of a three-phase SAPF show outstanding results [150,183,191,[195][196][197][198][199][200], including dynamic response [201]. Critical analysis of the compensation results using the p-q, FBD, and GINAP methods showed that the GINAP method leads to very good performance even under conditions of a non-sinusoidal supply voltage and non-periodic load currents [194,202].…”
Section: Reference Current Generation For the Direct Controlmentioning
confidence: 99%
“…There is research on the influence of this time interval, depending on the compensation objective [146,193,194]. Implementations based on GINAP theory in the control of a three-phase SAPF show outstanding results [150,183,191,[195][196][197][198][199][200], including dynamic response [201]. Critical analysis of the compensation results using the p-q, FBD, and GINAP methods showed that the GINAP method leads to very good performance even under conditions of a non-sinusoidal supply voltage and non-periodic load currents [194,202].…”
Section: Reference Current Generation For the Direct Controlmentioning
confidence: 99%